What Should Business Schools Teach Managers?. (1st March 2013) - Parker, Martin; Pearson, Gordon
Abstract: This article is the fourth dialogue in a series in which two characters, a pro‐business experienced manager and a critical management academic idealist, debate contemporary management. In this dialogue, the discussion concerns the curriculum of business and management courses. Though as usual there is little agreement between the two participants, the discussion clearly shows just how difficult it will be to change business education without also changing the market position of business schools. Other topics concern the sort of economic assumptions embedded in much of the curriculum, and the relationship between practical skills and political descriptions of capitalism.